Micropropagation of Clerodendrum serratum L. through Direct and Indirect Organogenesis - Vidya, SM; Krishna, V; Manjunatha, BK; Pradeepa, MR (Plant Tissue Culture and Biotechnology, 2013)
In vitro clonal propagation of Clerodendrum serratum L., a rare medicinal plant has been reported by using LM medium supplemented with different growth hormones. The maximum number of shoots with maximum length were obtained from stem derived callus on LM media fortified with 1.5 mg/l BAP and 0.3 mg/l NAA. Nodal explants showed direct organogenesis on LM media containing BAP (0.5 mg/l) alone. The regenerated shoots were successfully rooted with maximum frequency (100%) on half strength LM media supplemented with 0.5 mg/l NAA. The well rooted microshoots were successfully transferred to hardening and survival rate was 88%. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14208 Plant Tissue Cult. & Biotech. 22(2): 179-185, 2012 (December)